PENGARUH ATRIBUT PRODUK PAKAIAN TERHADAP WEB BROWSING HEDONISM DAN PEMBELIAN IMPULSIF - Suarmaja, I.B Koman; Wardana, Made; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
This study aims to explain the effect of apparel product attributes to web browsing hedonism and impulsive buying at B2C shopping site in Denpasar. An online questionnaire used as an instrument of primary data collection. Sampling technique used is purposive sampling by the respondents as many as 100. The hypothesis testing used analytical techniques Partial Least Square (PLS) by SmartPLS 3. The results showed that the variety of selection and price policy and significant positive effect on web browsing hedonism, sensory attributes not significant effect on web browsing hedonism. Variety of selection and significant negative effect on impulsive buying. Pricing policy, sensory attributes and web browsing hedonism positive and significant effect on online impulsive buying.Web browsing hedonism is found as a mediating influence variety of selection and pricing policy on impulsive buying. Marketers website should not provide too many product choices, as well as considering the use of virtualization technology products in 3D to provide more information in real clothing products on shopping sites that evoke passion hedonist visitors during web browsing.
Keywords: apparel product attributes, web browsing hedonism, impulsive buying